Evolution of Trans-Social Entrepreneurship in India : An Untold Journey from 1990–2025 - Diwakar, Komal; Bhalla, Pretty (Prabandhan: Indian Journal of Management, 2026)
Background : According to the Census of 2011, there were approximately 5 lakh transgender people in India. Furthermore, a report prepared by the National Human Rights Commission (2018) showed that 96% of transgender people are denied employment because of gender discrimination. In coming up with ways to solve the unemployment problem, we had numerous accounts of transgender social entrepreneurs who are self-employed and were generating jobs for their community members. Purpose : This paper explored the development of transgender social entrepreneurship in India (1990–2025) to gain insights into how such enterprises can generate livelihoods, cut down unfair discrimination-based unemployment, and promote social inclusion. It also emphasized the centrality of these businesses and supplied a justification for the model of inclusive policies. Methodology : The paper adopted an exploratory research design, extensively utilizing secondary data from government reports, media, and organizational records. Fifty transgender-owned or managed businesses in 13 States/UTs of India were mapped and analyzed to find out the temporal, regional, and sectoral patterns. Findings : The analysis showed a consistent increase in food, hospitality, beauty and wellness, and social service ventures, which demonstrated strong resistance in the face of systemic discrimination. Not only were transgender entrepreneurs self-employed, but they were also creating jobs, providing role models, and bringing about social change. Practical Implications : The results provided evidence-based recommendations for policymakers, NGOs, and investors on how to plan specific funding, training, and skill development interventions to support trans-led businesses and advance the UN Sustainable Development Goals on gender equality and decent work. Originality/Value : Empirical studies on transgender entrepreneurship in India remain rare. This first longitudinal mapping of trans-social enterprises offered a baseline dataset and analytical framework for future research while validating the economic and social potential of the transgender community.